The Role of Human Resource Management in Family to Build Children's Social Character (Comparative Study of Families in Jakarta) - Evy Clara; Syaifuddin Syaifuddin (Universitas Pendidikan Ganesha, 2023)
The influence of modern lifestyles and behavior as a result of interactions between civilizations in this world is quite complex, both in terms of type and target, such as children. Consequently, one of them affects the value and understanding of religion and social interaction in society, even in the smallest unit in society, namely the family. In fact, family is the most important primary group in society. The purpose of this study was to analyze the role of resource management in the family to build children's social character. This research is qualitative research with non-probability sampling. Primary data collection was carried out through interviews and observation, while secondary data collection was carried out using data sources through literature studies and documentations. The data in this study was analyzed by data organization, data processing, data interpretation, and conclusions. Based on research results, the role of parents in instilling values ​​and norms to build strong personality and character in children is very important, both related to the values ​​of religious moderation (tolerance, diversity, and harmony), piety, integrity, responsibility, discipline, hard work, creativity, and national insight. Children’s strong social character is not only useful for themselves to filter out bad environments, but also to be the basis for carrying out rights and obligations as members of society, as well as making advancement for the nation and state.